Perancangan Sistem Informasi Penjualan Berbasis Web (Studi Kasus : Toko Citra Azka Bila) - Redha Juliansyah; Endar Nirmala (CV. Multi Kreasi Media, 2024)
Internet technology has a huge effect on commerce or business. Only from where the prospective buyer holds the cellphone, the prospective buyer can view the products on the computer screen, and access the information, order and pay with the available options. Citra Azka Store If it is engaged in wholesale and unit buying and selling, starting from basic goods, basic necessities, snacks and so on and the implementation of buying and selling is still done traditionally, therefore a web-based sales system is designed with the aim of reaching more consumers and reaching consumers who are wider. The method used in this research is Rapid Application Development (RAD) because the developed application does not require a long time to develop and supports designing applications in a relatively short period of time. This research resulted in a web-based sales information system application at the Citra Azka Bila Store using UML design and developed using HTML and CSS programming languages, PHP, and MySQL as the database server, and Black Box as the testing method.